PEMANFAATAN KAPUK RANDU SEBAGAI PRODUK INTERIOR DI DESA ADAT UNGASAN - Ni Luh Yogiswari Ananda Laksmi; A.A.Ngr.Eddy Supriyadinata Gorda; Ida Ayu Oka Martini; Luh Putu Mahyuni (LP2M Universitas Hasanuddin, 2023)
Kapok Randu has been used by kapok craftsmen in the Ungasan Traditional Village, Badung Regency, Bali Province, as mattress products and products for religious ceremonies. Currently, product sales are declining significantly. This is due to several factors, such as the production process is still traditional; the product design could be more complex and attractive. New product design innovation is needed to restore sales of this craft product. This community outreach program is carried out to introduce and train kapok craftsmen to create a more innovative and attractive product; thus better meeting market tastes. With more innovative designs, it is expected that sales of kapok products will be increased. The results of this community outreach program are: (1) Increase in the understanding of craftsmen on the importance of product innovation; (2) An increase in the skill of craftsmen in making an innovative new product, in this case in the form of attractive sofa cushions as an interior product; (3) There was a significant change in the design of kapok products before and after implementing a community outreach program. Product design becomes more innovative, attractive, and better at meeting market tastes. — Kapuk randu selama ini telah dimanfaatkan oleh pengrajin kapuk di Desa Adat Ungasan Kabupaten Badung, Provinsi Bali sebagai produk kasur dan produk untuk upacara keagamaan. Saat ini penjualan produk mengalami penurunan secara signifikan. Beberapa faktor penyebabnya antara lain: proses produksi yang masih tradisional; desain produk yang sangat sederhana dan kurang menarik. Inovasi desain produk baru dibutuhkan untuk dapat mengembalikan penjualan produk kerajinan ini. Kegiatan pengabdian kepada masyarakat ini dilakukan untuk memperkenalkan dan melatih pengrajin kapuk membuat produk berbahan kapuk dengan desain yang lebih inovatif dan menarik, sehingga dapat memenuhi selera pasar. Dengan desain yang lebih inovatif diharapkan penjualan produk berbahan kapuk akan dapat ditingkatkan. Hasil dari kegiatan pengabdian kepada masyarakat ini berupa: (1) peningkatan pemahaman pengrajin akan pentingnya inovasi produk; (2) peningkatan keterampilan pengrajin membuat produk baru yang inovatif berupa bantal sofa sebagai produk interior; dan (3) perubahan nyata pada desain produk berbahan kapuk antara sebelum dan setelah dilaksanakannya kegiatan pengabdian kepada masyarakat. Desain produk menjadi lebih inovatif, menarik, dan memenuhi selera pasar.